Symbolic Compliance in Digital Government Accounting: Ethnomethodological Insights from Ministry of Finance Officials - Devi Kusumawardhani; Nur Kholya (Universitas Tidar, 2026)
This research focuses on symbolic compliance in the implementation of digital government accounting practices within the Ministry of Finance of the Republic of Indonesia. Using a qualitative approach based on ethnomethodology, this study focuses on how organizational actors understand and implement accounting practices in their daily activities. Data were collected through in- depth interviews with ten informants from Echelon I and II levels. Accounting practices are still heavily influenced by the procedural demands inherent in the system. The main findings of this study indicate that symbolic compliance practices remain quite strong. In many cases, compliance is not solely carried out to achieve substantive organizational goals, but rather as an effort to meet institutional expectations and maintain legitimacy. Audit pressures and regulatory arrangements further reinforce this tendency, as formal compliance is often positioned as a key indicator of performance. The study also found a gap between formal structures and daily practices. Despite the systems being designed, decision-making processes have not fully utilized the data generated. This situation creates a paradox: data is available in large quantities, yet its use for analysis remains limited. The findings indicate that accounting systems extend beyond control functions, as they also influence organizational legitimacy and the way organizations understand their practices. Therefore, digital transformation should not be understood solely as the application of new technologies, but rather as a social and institutional process that also changes work practices and how organizations interpret their activities. This research shows that accounting systems function not only as a control tool but also as a means of legitimacy that shapes organizational thinking. Therefore, digital transformation needs to be understood as a socio-institutional process, not simply a technological development.